On the Use of the Correlation between Acoustic Descriptors for the Normal/Pathological Voices Discrimination. (7th June 2009) - Dubuisson Dubuisson, Thomas Thomas; Dutoit Dutoit, Thierry Thierry; Gosselin Gosselin, Bernard Bernard; Remacle Remacle, Marc Marc
Abstract : This paper presents an analysis system aiming at discriminating between normal and pathological voices. Compared to literature of voice pathology assessment, it is characterised by two aspects. First the system is based on features inspired from voice pathology assessment and music information retrieval. Second the distinction between normal and pathological voices is simply based on the correlation between acoustic features, while more complex classifiers are common in literature. Based on the normal and pathological samples included the MEEI database, it has been found that using two features (spectral decrease and first spectral tristimulus in the Bark scale) and their correlation leads to correct classification rates of 94.7% for pathological voices and 89.5% for normal ones. The system also outputs a normal/pathological factor aiming at giving an indication to the clinician about the location of a subject according to the database.